BRAZILIAN DIGITAL PUBLIC ADMINISTRATION: A CRITICAL ANALYSIS OF THE DUTY OF EFFICIENCY AND THE APPLICATION OF NEW TECHNOLOGIES - Edstron S. Santos, Júlio (Revista Gênero e Interdisciplinaridade, 2026)
This research analyzes technological implementation in Brazilian Public Administration not as a discretionary power, but as a binding legal duty rooted in the principle of efficiency. In a scenario of liquid modernity, bureaucratic obsolescence threatens state legitimacy, making digital transformation urgent for guaranteeing fundamental rights. Methodologically, the hypothetical-deductive method was employed, supported by a robust interdisciplinary bibliographic review and critical analysis of federal, state, and municipal experiences. The investigation contrasted successes in digital governance with failures stemming from exclusion and algorithmic bias, highlighting the tension between modernization and accessibility. The results confirm that technological inertia constitutes unconstitutionality by omission, violating the fundamental right to good administration. It is concluded that national sovereignty and full citizenship depend on the construction of a Digital Rule of Law, where technology acts as vital infrastructure for procedural celerity, algorithmic transparency, and social inclusion, requiring governance that harmonizes innovation with data protection and constitutional humanistic values.